Quantal analysis of inhibitory synaptic transmission in the dentate gyrus of rat hippocampal slices: a patch-clamp study. - Edwards, F A (1990)
1. Synaptically connected neurones were identified in the granule cell layer of slices of 17- to 21-day-old rat hippocampus. Whole-cell current recording using the patch-clamp technique revealed synaptic currents ranging from less than 10 to 200 pA in symmetrical Cl- conditions, at a holding potential of -50 mV. These currents were blocked by 2 microM-bicuculline, indicating that they result from the activation of postsynaptic gamma-aminobutyric acid receptor (GABAA-receptor) channels. 2. Addition of tetrodotoxin (TTX, 1 microM) resulted in the loss of most currents of more than 40 pA in amplitude. Currents which disappeared after TTX treatment were assumed to be the result of spontaneous presynaptic action potentials. The currents seen in the absence of TTX are referred to as spontaneously occurring inhibitory postsynaptic currents (IPSCs); those remaining in the presence of TTX were defined as miniature IPSCs. 3. Similar currents were observed when recording in the whole-cell configuration while extracellular stimulation was applied to a nearby neurone. These currents were also completely blocked by 2 microM-bicuculline and by 0.5 microM-TTX. They were thus defined as stimulus-evoked IPSCs. 4. The half rise time of both miniature and stimulus-evoked IPSCs was fast (less than 1 ms). The time course of decay of both miniature IPSCs and stimulus-evoked IPSCs could be well fitted with the sum of two exponentials. At a membrane potential of -50 mV, the mean decay time constants of the two components were 2.0 +/- 0.38 and 54.4 +/- 18 ms (mean +/- S.D.) for miniature IPSCs (six cells) and 2.2 +/- 1.3 and 66 +/- 20 ms (three cells) for stimulus-evoked IPSCs. 5. Stimulus-evoked IPSCs varied in amplitude from less than ten to hundreds of picoamperes. In eight of eleven cells histograms of IPSC amplitudes showed several clear peaks which, when fitted with the sum of Gaussian curves, were found to be equidistant. This is consistent with the view that stimulus-evoked IPSC amplitudes vary in a quantal fashion. The quantal size varied between 7 and 20 pA, at a membrane potential of -50 mV. 6. Decreasing the Ca2+ and increasing the Mg2+ concentration in the extracellular solution decreased the number of peaks in the IPSC amplitude histogram but did not affect the size of the quantal event.(ABSTRACT TRUNCATED AT 400 WORDS)